Analysis of Oyster Mushroom (pleurotusostreatus) (The Case of Oyster Mushroom Farmers in Peguyangan KajaVillage, North Denpasar Sub-District) - SAHADEWA, IDA BAGUS; DEWI, RATNA KOMALA; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.2, April 2019, 2019)
Analysis of Oyster Mushroom (pleurotusostreatus) (The Case of Oyster Mushroom Farmers in Peguyangan KajaVillage, North Denpasar Sub-District) The development of oyster mushrooms (pleurotusostreatus) is enough to encourage mushroom farming in Indonesia. The same thing was done by the farmers of PeguyanganKaja Village, North Denpasar Sub-District, who were involved in oyster mushroom farming. This research was conducted in August 2017 through December 2017. The purpose of this study was to determine the feasibility of oyster mushroom business, analyzed using Net Present Value (NPV) investment criteria, Net benefit cost ratio (Net B / C), Internal rate of return (IRR), Payback Period (PBP), and Sensitivity analysis and knowing the constraints experienced by farmers in cultivating oyster mushrooms. Based on the research and the results of the analysis that has been done, the following conclusion can be arrived at. Oyster Mushroom Farming with a capacity of 1.000, 2.500, 3.000, 5.000 and 6.000 baglogs worthy of being farmed with an interest rate of 12%, this is aimed at NPV> 0 (positive), Net B / C> 0 (positive), IRR> i that is 12%, and PP <Economic age of mushroom media (5 years) and, sensitivity analysis based on the three sensitivity analyses, oyster mushroom farming at media mushroom capacity 5,000 baglogs is not sensitive to, increases in operational costs, decreases in production quantity and decreases the selling price of 10%. Constraints faced in the cultivation of oyster mushrooms in the village of PeguyanganKaja, which is lowland, are that it is difficult to obtain a level of humidity between 80% and 100%, which of course is easier to do if it is in the highland.